The Effect of Liquid Organic Fertilizer of Rabbit Urine and Concentration of Plant Growth Promoting Rhizobacteria of Bamboo Root on the Growth and Yield of Mustard Green Plants - Latifah, Nurul; Setiyono; Muhlison, Wildan; Sucipto, Irwanto; Savitri, Dyah Ayu; Patricia SM, Susan Barbara; Arum, Ayu Puspita (Journal La Lifesci, 2022)
Mustard greens (Brassica juncea L.) are one type of favorable vegetable. However, mustard greens production and productivity still fluctuate. Also, society expects quality, healthy and safe vegetable products for consumption. So, it is necessary to increase the use of organic fertilizers to produce high productivity and good products. LOF of rabbit urine contains high nutrients, and PGPR contains microorganisms that act as bioactivators that decompose organic matter. This study aimed to determine the effect of giving LOF of rabbit urine and concentration of PGPR of bamboo roots on the growth and yield of mustard greens. The experiment was carried out factorially using Random Design Complete with three replications. The first factor was the LOF dose of rabbit urine, and the second was the PGPR concentration which consisted of 4 levels. The results showed that (1) the interaction of LOF of rabbit urine and concentrations of PGPR of bamboo root had no significantly different effect on all variables; (2) LOF of rabbit urine had no significantly different effect on all variables and (3) PGPR concentration of bamboo roots had a significant different effect on all variables except root volume and number of leaves, where treatment of 15 ml/L (B3) gave the best results on the yield of mustard greens.